DEEP TALK AS A MODEL OF ISLAMIC FAMILY COMMUNICATION: A CASE STUDY OF SYAFIQ RIZA BASALAMAH - Umar Ali; M. Wahid Abdullah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Deep talk is a form of in-depth communication that emphasizes openness, empathy, and reflective dialogue within family relationships. Family harmony refers to a relational condition characterized by tranquility (sakinah), love (mawaddah), and compassion (rahmah) through healthy and mutual communication. This study aims to analyze the implementation of deep talk in fostering family harmony based on the da'wah practices of Syafiq Riza Basalamah as the main respondent. The research employs a qualitative approach with a case study method, involving one primary informant and 8 supporting informants (husbands/fathers and children). Data were collected through in-depth interviews, documentation, and source triangulation. The findings indicate that deep talk is implemented through the principle of “connection before correction,” the use of strategic moments such as before bedtime and during travel, and a dialogical and non-judgmental approach in marital and parent-child relationships. This practice effectively enhances openness, emotional closeness, empathy in practicing birrul walidain (filial piety), and constructive conflict resolution. Deep talk is also aligned with Islamic values and the objectives of Islamic law (maqashid al-shariah) in establishing a sakinah, mawaddah, wa rahmah family, although its effectiveness depends on emotional readiness and the consistency of family members.